A study on foreign exchange investment trading strategies applied in mutual element concept / Farah Dhamirah Hamzah - Hamzah, Farah Dhamirah (Faculty of Business and Management, 2011)
This study is conducted in order to analyze the foreign exchange investment trading strategies that been applied in MEC. The study is to analyze the foreign exchange investment trading strategies that have been used and applied in the MEC Company. These study also to classify the gap between the theory and practice of the company foreign investment trading strategies. However, instead of identifying the gap, this study also is to suggest and give ideas on improving the company trading strategies method to be more efficient and effective. Then, source of information used in this study are primary data which basically gathered during training session. While secondary data been gathered through internal sources of the company, books, and journals. Basically, this study used stop loss and profit lock-in as the method of analysis which important as risk management in investment trading strategy. Otherwise, there are indicator such as Bollinger Band, Parabolic SAR, and also Relative-Strength Index with Alert which also important in risk management strategy. Thus, the foreign exchange investment trading is the over the counter market with a vast network of interrelated traders, market places and different currency instruments.